Monitoring of flood extent dynamics using remote sensing and GIS - Yaianong Thimsuwan; Kaew Nualchawee; Honda, Kiyoshi; Schumann, Robert; Ministry of University Affairs of Thailand (Bangkok : Asian Institute of Technology, 1997)
The Chao Phraya River basin, an important and high economic area of Thailand, has frequently experienced flooding every 2-3 years, resulted in extensive flood damage and loss of human life. In the past few decades, rapid urbanization in Bangkok and provincial cities as well as the intensification of agriculture have increased potential flood damages. Following the most severe recent flood in 1995, the government has intensified its eforts to lowers flood risks by initiating many flood protection and flood management projects. Although the extent of flooding may be reduced by various purposed flood control infrastructure, the effective flood management schemes are still necessary to be studied and implemented, resulted in the requirement of data on reliable flood extent area and its movement which is quite difficult to obtain. This study aims to fulfil such requirement by using satellite imageries, providing real spatial information, through GIS for detection of flood extent area and its dynamic in lower Chao Phraya River basin. Optical Landsat TM and SAR JERS-1 and ERS-1 images of different dates from the beginning of rainy season to the end of flood period in 1995 were processed in the study in order to classify the present landuse and identify the flood extent areas in October and November. The results of landuse map as well as flooded area maps obtained in the study reveals that combination of information extracted from various sensors with different characteristics can supplement each other in identifying the permanent water and the flood extent areas including the flood extent dynamic by employing images on different dates. Although, it is rather difficult to assess the real accuracy of the results obtained in the study due to the rare existing ground truth of such information, the flood extent dynamic map obtained provide useful information for the better understanding of flood phenomena in the lower Chao Phraya River basin which is consequently important basic information for flood management projects for flood alleviation in this area.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1997
Keywords: Geographic information systems; Flood forecasting -- Remote sensing